2010
DOI: 10.1002/jssc.201000351
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐diffusion microextraction

Abstract: Gas-diffusion microextraction (GDME) is an innovative technique that combines the advantages of membrane-aided gas-diffusion with microextraction concepts. GDME makes uses of a novel portable and low-cost device that comprises a small, commercially available, semi-permeable membrane. Furthermore, if derivatization is integrated into the GDME concept, considerable enrichment factors can be obtained. It may become a powerful tool for any analyst who intends to quantify volatile and semi-volatile analytes in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 37 publications
0
44
0
2
Order By: Relevance
“…Next, there is the mass transport by diffusion of volatile analytes through such gas layer that separates the two liquids (donor and receptor solutions). As only few compounds are sufficiently volatile at specific temperatures, the gas diffusion increases the selectivity of the analytical platform [32]. Furthermore, the membranes can be coupled in systems by flow injection analysis (FIA) to enable continuous monitoring [3,33].…”
Section: Introductionmentioning
confidence: 99%
“…Next, there is the mass transport by diffusion of volatile analytes through such gas layer that separates the two liquids (donor and receptor solutions). As only few compounds are sufficiently volatile at specific temperatures, the gas diffusion increases the selectivity of the analytical platform [32]. Furthermore, the membranes can be coupled in systems by flow injection analysis (FIA) to enable continuous monitoring [3,33].…”
Section: Introductionmentioning
confidence: 99%
“…The volatile compounds (or their precursors), arising from raw materials and/or produced during brewing pro-Several approaches have been employed to extract and concentrate beer volatile components, such as LLE [11], simultaneous extraction and distillation [12], SPE [13], SFE [14], gas-diffusion microextraction [15] and more recently SPME [4,5,[16][17][18][19][20][21][22][23][24][25][26]. Actually, over the last two decades, microextraction techniques, such as SPME, have been developed to promote a rapid and efficient sample preparation [27], and is a solvent-free technique.…”
Section: Introductionmentioning
confidence: 99%
“…Previous published works showed that GDME is mainly affected by time and temperature of extraction [16,21,22]. Results of the influence study of these parameters in the extraction of AA are presented in Fig.…”
Section: Extraction Optimizationmentioning
confidence: 85%
“…In this work, AA was determined using gas-diffusion microextraction (GDME) [20,21] and high-performance liquid chromatography with spectrophotometric detection (HPLC-UV), applying pre-column derivatisation with 2,4-dinitrophenylhydrazine (DNPH). GDME is a recently developed extraction technique that allows a simple and quick extraction of volatile and semi-volatile analytes for analytical purposes.…”
Section: Introductionmentioning
confidence: 99%